Carbene Footprinting Reveals Binding Interfaces of a Multimeric Membrane‐Spanning Protein. Issue 47 (20th October 2017) - Manzi, Lucio; Barrow, Andrew S.; Hopper, Jonathan T. S.; Kaminska, Renata; Kleanthous, Colin; Robinson, Carol V.; Moses, John E.; Oldham, Neil J.
Abstract: Mapping the interaction sites between membrane‐spanning proteins is a key challenge in structural biology. In this study a carbene‐footprinting approach was developed and applied to identify the interfacial sites of a trimeric, integral membrane protein, OmpF, solubilised in micelles. The diazirine‐based footprinting probe is effectively sequestered by, and incorporated into, the micelles, thus leading to efficient labelling of the membrane‐spanning regions of the protein upon irradiation at 349 nm. Areas associated with protein–protein interactions between the trimer subunits remained unlabelled, thus revealing their location. Abstract : A distinctive footprint : A carbene‐footprinting approach was used to identify the interfacial sites of a trimeric integral membrane protein solubilised in micelles. The diazirine probe was incorporated into the micelles and labelled the membrane‐spanning regions of the protein upon irradiation at 349 nm (see picture). Areas associated with protein–protein interactions between the trimer subunits remained unlabelled, thus revealing their location.